Implementation of the Pancasila Student Profile Strengthening Project in Shaping Student Character at SD Negeri 160 Palembang - Ahmat Kadafi; Meilia Rosani; Djunaidi Djunaidi (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) in shaping student character at SD Negeri 160 Palembang. As a core component of the Independent Curriculum (Kurikulum Merdeka), P5 is designed to reinforce the fundamental values of Pancasila in students.This study employs a qualitative case study method. Data were collected through direct observation, in-depth interviews, and documentation involving the principal, vice-principal of curriculum, classroom teachers, students, and parents. The results indicate that P5 implementation is carried out through three systematic stages: planning (team formation and theme selection), execution (applying experiential learning that encourages collaboration), and assessment. The three primary values emphasized are faith and morality, respecting differences, and togetherness. Despite challenges such as time constraints, synchronization of materials across subjects, and the need for teacher training, the study concludes that P5 is an effective instrument for character education. To optimize results, it is recommended to enhance program monitoring and align the conceptual understanding of P5 among educators. Overall, SD Negeri 160 Palembang has demonstrated a serious commitment to integrating P5 as a means of positive character building.